2011
DOI: 10.1007/s11010-011-0938-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic osteogenic growth peptide promotes differentiation of human bone marrow mesenchymal stem cells to osteoblasts via RhoA/ROCK pathway

Abstract: The osteogenic growth peptide (OGP) is a naturally occurring tetradecapeptide that has attracted considerable clinical interest as a bone anabolic agent and hematopoietic stimulator. In vitro studies have demonstrated that OGP directly regulates the bone marrow mesenchymal stem cells' (BMSCs) differentiation into osteoblasts. However, the exact mechanism of this process remains unknown. In the present study, we investigated the role of RhoA/ROCK signaling in differentiation along this lineage using human BMSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 28 publications
1
54
0
Order By: Relevance
“…Gi-independent S1P/S1PR2 signaling also activates RhoA/Rho kinase (ROCK) in smooth muscle cells and CHO cells [19,20]. Interestingly, the RhoA/ROCK signaling pathway regulates both cytoskeletal dynamics [21] and osteoblast differentiation [22,23]. However, whether S1P/S1PR2-mediated signaling-including S1PR2-mediated RhoA/ROCK signaling-plays a role in osteoblast differentiation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Gi-independent S1P/S1PR2 signaling also activates RhoA/Rho kinase (ROCK) in smooth muscle cells and CHO cells [19,20]. Interestingly, the RhoA/ROCK signaling pathway regulates both cytoskeletal dynamics [21] and osteoblast differentiation [22,23]. However, whether S1P/S1PR2-mediated signaling-including S1PR2-mediated RhoA/ROCK signaling-plays a role in osteoblast differentiation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Tibial curettage and administration of BMP-2 to animals were used as osteogenesis-inducing stimuli. Curettage is an adequate model for investigation of the mechanisms of post-traumatic regeneration of the bone tissue: it induces systemic increase in MSC level [4] and their osteogenic activity due to growth factors release into circulation [5]. BMP-2 induces a cascade response leading to chondrogenesis, osteogenesis, angiogenesis, and controlled synthesis of the extracellular matrix [14].…”
mentioning
confidence: 99%
“…Previous studies showed that RhoA/ROCK signaling played a key role in the regulation of osteogenesis [16][17][18]. Results showed that after 24 h of culture, 0.5 mM DMOG increased the expression of GTP-bound RhoA (P < 0.001 vs. control group).…”
Section: Dmog Promoted Active-rhoa Protein Expression and Increased Rmentioning
confidence: 85%
“…Indeed, Wang et al [16] reported that bone morphogenic protein (BMP) promotes human mesenchymal stem cell (MSC) osteogenesis by altering cytoskeleton via activation of RhoA/ROCK signaling. Other studies showed that osteogenic growth peptide (OGP) [17], connective tissue growth factor [18], extracellular matrix [19], and hydrostatic pressure [20] promote the osteogenic differentiation of human bone marrow MSC (BMSC) via RhoA/ROCK signaling activation.…”
Section: Introductionmentioning
confidence: 99%